Maps of abiotic stresses for rice in Africa - CGIAR Research Program on Rice (2019)
Maps of abiotic stresses for rice was published in Field Crops Research, and can be useful for prioritizing research and identifying stress hotspots, for directing technologies and varieties to those areas where they are most needed.